Development of a Lateral Flow Immunoassay for the Rapid Diagnosis of Invasive Candidiasis - He, Zheng-Xin; Shi, Lan-Chun; Ran, Xiang-Yang; Li, Wei; Wang, Xian-Ling; Wang, Fu-Kun (Frontiers in Microbiology, 2016)
Early and accurate diagnosis of invasive candidiasis (IC) is very important. In this study, a lateral flow immunoassay (LFIA) was developed to detect antibody against Candida albicans enolase (Eno). Colloidal gold particle labeled mouse anti human IgG (1.0 mg/L) was used as the detector reagent. Recombinant enolase (rEno, 1.0 mg/L) and goat anti IgG (1.0 mg/L) were immobilized in test and control lines, respectively, of a nitrocellulose membrane, acting as the capture reagents. The LFIA was used to detect anti Eno in 38 sera from clinically proven IC patients, as well as in 50 healthy control subjects. Compared with an indirect ELISA designed as a reference test, the specificity and sensitivity of the LFIA were 98.2 and 84.8%, respectively. Excellent agreement between the results obtained by ELISA and the LFIA (κ = 0.851) was observed in this study. In addition, the agreement between the blood culture results and LFIA test is strong (κ = 0.658). The data presented in the study indicate that the LFIA test is a suitable tool for the serological surveillance of IC in the field or in poorly equipped laboratories.